Analysis of Accounting Understanding and Tax Awareness in Madura Coastal Tourism MSME Actors - Lutfia, Citra; Zakiyah RF, Rahayu Dewi (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
This study seeks to reveal the accounting understanding and tax awareness of MSME actors in the north coast of Sampang Regency. The method used is mixed method. The population in this study were MSME actors in the north coastal area of Sampang Regency, the sampling technique used the census method with 49 respondents. Data collection was carried out by distributing questionnaires at the location. The data were analyzed using descriptive statistics. Furthermore, interviews were conducted with MSME actors in the north area of Sampang Regency. The results showed that the accounting understanding and tax awareness of MSME actors in the north coastal area of Sampang Regency were in the high category, but these results contradicted the results of interviews conducted as a form of confirmation. The results of interviews related to understanding accounting of MSME actors still cannot understand the concepts of accounting and tax awareness.